A Study of the Various Waqf Model in the Ottoman History - Aam; Denizar Mi'raj (Islamic Economics and History, 2022)
This paper seeks to determine the evolution of waqf research during the Ottoman period. Utilizing secondary data in the form of articles published and indexed by Scopus between 1979 and 2022, processed with Microsoft Excel 16 and analyzed with Nvivo 12 Plus software to automatically perform coding and classification in order to organize the file structure, the method employed is qualitative. The outcomes of this study reveal an upward trend in Islamic economic studies related to halal requirements. The majority of the 96 published papers said that the most prevalent halal food standard and the evolution of halal standards cannot be separated from halal certification. Waqf, Ottoman, Waqfs, Study, Islamic, Foundations, Critical, Century, Edition, and Institutions are the words that appear most frequently in publications with conventional halal themes. In addition to these words, the word woman also appears, indicating that these women played a part in the creation of waqf during the Ottoman period. This research is anticipated to contribute to the expansion of academic studies on ottoman waqf, which are currently limited. Additional study pertaining to ottoman waqf might refer to the discoveries of frequently occurring words since they have the possibility to be expanded.